Short commercialization circuits: the game between the available and the possible in family farming - Paz, Raúl Gustavo (2020)
Short commercialization circuits constitute new ways of organizing family farming. However, when they are understood only from a farmer’s market perspective, the production logic supporting the commercialization process gets diluted. This article aims to identify the dynamics generating short circuits developed by a farming family in an everyday context in Santiago del Estero (Argentina). Two examples of these circuits are analyzed: one under a farmer’s market context and the other during a pandemic. This study will attempt to demonstrate that the constructions of such commercial mechanisms respond to a balance between the available reality (in terms of endogenous and exogenous resources, market, social networks, technology, own knowledge, etc.) and the possibilities that allow the potential of family agriculture. The methodology used was qualitative, while the techniques were field visits, in-depth interviews, and direct observations.